The profits of doom: agriculture, construction, water and land use in Jaffna Peninsula - Nesiah, D.; Rajasooriyar, L.D.; Jayasingam, T. (My University, 2005)
The fresh water problem in Jaffna has engaged the attention of scholars and community leaders for over a century, and specific remedies, including the progressive desalination of the lagoons, have been explored for over half a century. Various investigations have been carried out and corrective measures tried out from time to time, but these have been neither comprehensive no sustained. Jaffna has long been noted for its distinctive system of intensive, lift irrigated cultivation, particularly of tobacco and certain subsidiary food crops; and Jaffna farmers for their capacity to extract maximum profits from their mini-plots through high yields and rotational cropping, for their willingness to experiment with new crops and novel techniques, and for their quick response to change (and impending changes) in the market. Overall, agriculture in Jaffna had been profitable till the outbreak of the civil war in the mid 80s. But Jaffna has no rivers or lakes, and water for irrigation and domestic use is extracted from wells or from rain. Over extraction led to increased salinity compounded by extensive mining of limestone for the cement industry or directly in to construction, and over use of agro-chemicals to serious contamination of well water. Almost everywhere, well water was gradually turning saline and polluted. There are 20,000 open wells, and 30,000 households are supplied pipe borne water by the municipal authorities. The demand for such supply exceeds the availability. The pollution problem is even more serious. The peculiar nature of the Miocene limestone aquifer in much of the peninsula is such that the bulk of the agro-chemical used percolates in to it and much of it, in due course, is directly or indirectly consumed by humans. Thus the short term profits based on over use of water and agro-chemicals were leading Jaffna inexorably to doom when the civil war intervened. With the suspension of the civil war, the re-opening the A9 high way, the mine clearing, the gradual return of the displaced, the progressive resumption of agriculture and possible reconstruction of the cement factory, the specter of renewed deterioration in the quantity and quality of fresh water may again hover over the peninsula. The paper explores the available data in the light of recent developments and new research, identifies and analyses various policy
Keywords: Profits; Agriculture; Water; Land use